2018
DOI: 10.4236/ijohns.2018.74020
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life after Functional Endoscopic Sinus Surgery in Patients with Chronic Rhinosinusitis

Abstract: Chronic Rhinosinusitis (CRS) is a group of disorders characterized by the inflammation of mucosa of the nasal passages and paranasal sinuses. It includes chronic rhinosinusitis with polyps, CRS without polyps and Allergic Fungal Sinusitis (AFS). This debilitating disease causes negative impact on quality of life (QOL) of patients. Functional endoscopic sinus surgery (FESS) is the mainstay of surgical treatment for patients and improves QOL of patients. This subjective assessment of QOL can be measured by disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…FESS significantly reduced the mean score of all items in the SNOT-22 questionnaire in this study. M Junaid., et al [6] also showed significant improvement in the mean scores after FESS from 52.31 in SNOT-22 before surgery to 13.69 1 month after surgery.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…FESS significantly reduced the mean score of all items in the SNOT-22 questionnaire in this study. M Junaid., et al [6] also showed significant improvement in the mean scores after FESS from 52.31 in SNOT-22 before surgery to 13.69 1 month after surgery.…”
Section: Discussionmentioning
confidence: 83%
“…Researchers have shown interest in assessing QOL by developing QOL related questionnaires such as SNOT-22 that is deemed as the most suitable and reliable disease specific questionnaire designed for use in chronic rhino-sinusitis patients. It is a patient-reported outcome measure of symptom severity and quality of life in patients with Sino nasal diseases [6].…”
Section: Introductionmentioning
confidence: 99%
“…Only three studies reported the recurrence of CRS [ 12 - 14 ]. The data collected indicate an overall CRS recurrence rate of 47/150 (31.33%) after an average follow-up period of nine months.…”
Section: Reviewmentioning
confidence: 99%
“…For instance, Qadeer et al demonstrated a gradual improvement in the mean score of QOL over a one-year follow-up period. The QOL score is reduced from 52.31 to 13.69, 11.26, 12.5, and 12.81 in postoperative 1st, 3rd, 6th, and 12th months, respectively [ 14 ]. A similar trajectory has been replicated in other studies outside the Middle East, such as Jayakrishna et al, who reported a mean change of 33.04 with p < 0.001, indicating a high significance [ 22 ].…”
Section: Reviewmentioning
confidence: 99%
“…Quality of life is a term integrating several aspects such as physical, psychological, social, economic and emotional dimensions. The disturbance in any one of these aspects will, in turn, affect QOL significantly [16]. The study conducted by Almalki et al [4,9] found that some demographic factors such as age, sex, experience and level of abroad.…”
Section: Literature Reviewmentioning
confidence: 99%